2017
DOI: 10.1002/jsfa.8347
|View full text |Cite
|
Sign up to set email alerts
|

Seed priming with KNO3 mediates biochemical processes to inhibit lead toxicity in maize (Zea mays L.)

Abstract: Maize accumulates more Pb in roots than shoot at early growth stages. Priming of seeds with KNO prevents Pb toxicity, which may be exploited to improve seedling establishment in crop species grown under Pb contaminated soils. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 62 publications
1
9
0
Order By: Relevance
“…On each sowing depth, results indicate significantly lower emergence in KNO3 primed seed compared to hydroprimed. This is in collision with findings of Nawaz et al (2017), who tested the effect of KNO3 and hydropriming on maize seed germination. In this study, no significant differences were observed in germination percentage and emergence index of hydroprimed and KNO3 primed maize seeds.…”
supporting
confidence: 65%
“…On each sowing depth, results indicate significantly lower emergence in KNO3 primed seed compared to hydroprimed. This is in collision with findings of Nawaz et al (2017), who tested the effect of KNO3 and hydropriming on maize seed germination. In this study, no significant differences were observed in germination percentage and emergence index of hydroprimed and KNO3 primed maize seeds.…”
supporting
confidence: 65%
“…Heavy metals are omnipresent pollutants of the environment, and their excessive level in arable soil can pose serious threats not only to normal plant growth and development but also to human health ( Nawaz et al, 2017 , 2022 ; Alamri et al, 2018 ; Deng et al, 2021 ). The release of toxic heavy metals in agricultural soil due to anthropogenic activities (mining, wastewater sludge, and pesticides) is the major cause of global heavy metal pollution ( Gill et al, 2013 ; Saleem et al, 2020a ; Irshad et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in cotton and maize ( Guan et al, 2009 ; Singh et al, 2018 ) revealed that priming can significantly promote seed germination and seedling growth, and improve germination performance and seedling establishment under abiotic stress ( Ellouzi et al, 2021 ). Many seed initiation methods have been established, including hormone priming, osmopriming, hydropriming, stratification, humidification, hardening, and thermal shock ( Nawaz et al, 2017 ). Common initiators are polyethylene glycol (PEG), salicylic acid (SA), abscisic acid (ABA), and gibberellic acid (GA3) ( Jisha et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Common initiators are polyethylene glycol (PEG), salicylic acid (SA), abscisic acid (ABA), and gibberellic acid (GA3) ( Jisha et al, 2013 ). Hormone priming is an efficient and cost-effective method, but is affected by several factors, such as plant species, seed viability, initiator concentration, and initiation method ( Nawaz et al, 2017 ). Therefore, it is crucial to determine the most effective seed priming agent and concentration to achieve the desired results.…”
Section: Introductionmentioning
confidence: 99%